2020
DOI: 10.3892/ijmm.2020.4760
|View full text |Cite|
|
Sign up to set email alerts
|

lncRNA KCNQ1OT1 promotes proliferation and invasion of glioma cells by targeting the miR‑375/YAP pathway

Abstract: The long non-coding RNA KCNQ1OT1 is generally recognized as an oncogenic molecule in several human malignant tumors. However, to the best of our knowledge, the role of KCNQ1OT1 in glioma has not been fully investigated. The current study aimed to probe the biological function of KCNQ1OT1 in human glioma cell lines and its mechanisms. The glioma cell lines U251 and U87-MG were used as cell models. Cell proliferation and apoptosis assays were used to measure the effects of different treatments on survival, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Another study shown that lncRNA KCNQ1OT1 promotes proliferation and invasion of glioma cells by targeting the miR-375/YAP pathway. The results indicated that KCNQ1OT1 was upregulated in glioma tissues compared with adjacent tissues, which was associated with poor prognosis (Ding et al, 2020).…”
Section: Mirna-long Non-coding Rna Interaction In Glioma: Research Ou...mentioning
confidence: 99%
“…Another study shown that lncRNA KCNQ1OT1 promotes proliferation and invasion of glioma cells by targeting the miR-375/YAP pathway. The results indicated that KCNQ1OT1 was upregulated in glioma tissues compared with adjacent tissues, which was associated with poor prognosis (Ding et al, 2020).…”
Section: Mirna-long Non-coding Rna Interaction In Glioma: Research Ou...mentioning
confidence: 99%
“…It was recently documented that miR-375 was expressed at low levels in glioma, and inhibited tumor growth and cancer cell proliferation (59). miR-375 has been reported to function in regulating glioma cell proliferation, with the addition of the miR-375 inhibitor enhancing cell proliferation in both U251MG and U87-MG cells (60). miR-375 is a multi-functional regulator in a diverse range of cellular pathways, which can regulate numerous functional genes (61).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has showed that KCNQ1OT1 can promote cell proliferation and migration [40]. KCNQ1OT1 was found to enhance glioma cell proliferation and invasion via regulating the miR-375/YAP pathway and thereby accelerated the progression of glioma [41]. Meanwhile, in colorectal cancer, KCNQ1OT1 can induce cell apoptosis by sponging miR-329-3p [42].…”
Section: Discussionmentioning
confidence: 99%